Screening for Delirium Using Family Caregivers: Convergent Validity of the Family Confusion Assessment Method and Interviewer-Rated Confusion Assessment Method - Steis, Melinda R.; Evans, Lois; Hirschman, Karen B.; Hanlon, Alexandra; Fick, Donna M.; Flanagan, Nina; Inouye, Sharon K. (Journal of the American Geriatrics Society (JAGS), 2012)
Objectives To explore agreement between the Family Confusion Assessment Method (FAM‐CAM) for delirium identification and interviewer‐rated CAM delirium ratings. Design Exploratory analysis of agreement. Setting Community. Participants Fifty‐two family caregivers and 52 elderly adults with preexisting impairment according to standardized cognitive testing. Measurements The interviewer‐rating for delirium was determined by fulfillment of the CAM algorithm Results The total sample included 52 paired CAM:FAM‐CAM assessments completed across 52 dyads of elderly adults with preexisting cognitive impairment and family caregivers. The point prevalence of delirium was 13% (7/52). Characteristics did not differ significantly between the groups with and without delirium. The FAM‐CAM questions that mapped directly to the original four‐item CAM algorithm had the best overall agreement with the interviewer‐rated CAM (kappa = 0.85, 95% confidence interval (CI) = 0.65–1.0), sensitivity of 88% (95% CI = 47–99%), and specificity of 98% (95% CI = 86–100%). Conclusion The FAM‐CAM is a sensitive screening tool for detection of delirium in elderly adults with cognitive impairment using family caregivers, with relevance for research and clinical practice.